2020
DOI: 10.1093/mnras/staa797
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of the phase lags associated with the type-C quasi-periodic oscillation in GRS 1915+105

Abstract: We present a systematic analysis of the phase lags associated with the type-C QPOs in GRS 1915+105 using RXTE data. Our sample comprises of 620 RXTE observations with type-C QPOs ranging from ∼ 0.4 Hz to ∼ 6.3 Hz. Based on our analysis, we confirm that the QPO phase lags decrease with QPO frequency, and change sign from positive to negative at a QPO frequency of ∼ 2 Hz. In addition, we find that the slope of this relation is significantly different between QPOs below and above 2 Hz. The relation between the QP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
119
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(140 citation statements)
references
References 59 publications
20
119
1
Order By: Relevance
“…When the QPO frequency descends below 2 Hz; that is, during the linear decay phase, the lag at the QPO frequency averages to zero lag, but the upper harmonic frequency shows hard lags. This behavior is consistent with earlier studies during the outburst phase (Reig et al 2000;Qu et al 2010;Pahari et al 2013;Zhang et al 2020), where the phase lag has a log-linear relationship with the QPO frequency and changes sign approximately at 2 Hz.…”
Section: The Exponential and Linear Decay Phasessupporting
confidence: 92%
See 1 more Smart Citation
“…When the QPO frequency descends below 2 Hz; that is, during the linear decay phase, the lag at the QPO frequency averages to zero lag, but the upper harmonic frequency shows hard lags. This behavior is consistent with earlier studies during the outburst phase (Reig et al 2000;Qu et al 2010;Pahari et al 2013;Zhang et al 2020), where the phase lag has a log-linear relationship with the QPO frequency and changes sign approximately at 2 Hz.…”
Section: The Exponential and Linear Decay Phasessupporting
confidence: 92%
“…Interestingly, similar behavior is seen in the transition from exponential and linear decay phases that display a transitional QPO frequency of 2 Hz. In addition, it has been found that the average QPO phase lag is positive above and negative below 2 Hz (Reig et al 2000;Lin et al 2000;Qu et al 2010;Pahari et al 2013;Zhang et al 2020), and a similar trend can be observed between the exponential and linear outburst decay phases. This effect has been attributed to a pivoting lag-energy spectrum with the lag increasing with energy for progressively lower QPO frequencies and decreasing for progressively higher QPO frequencies (Pahari et al 2013;Zhang et al 2020).…”
Section: Comparison With the Previous Low X-ray Flux Statessupporting
confidence: 52%
“…for QPOs; Lee & Miller 1998;Lee, Misra & Taam 2001;Kumar & Misra 2014). Karpouzas et al (2020) explain this for the kHz QPOs in neutron-star LMXBs, and Zhang et al (2020) for the type C QPOs in the BH candidate GRS 1915+105, but the same mechanism could apply for the broad-band component that we discuss here. A similar argument was discussed by Méndez, van der Klis & Ford (2001) for the dependence of the rms amplitude of the khz QPOs in the neutron-star LMXBs 4U 1728-34, 4U 1608-52, and Aql X-1.…”
Section: Anticorrelation Between the Fractional Rms Amplitude And Thementioning
confidence: 55%
“…The phase lags at the type-C QPO frequencies have been systematically investigated in Van den Eijnden et al (2017) and Zhang et al (2020), but a similar feature has not been reported. Perhaps this is because those observations were mostly of type-C QPOs in the hard state, while we find that such hard lags are specific to type-C QPOs observed during the relatively short-lived transition and are not seen as clearly in the hard state.…”
Section: Appendix a Lag-frequency Spectra Of Individual Epochsmentioning
confidence: 96%